PGV-1 permanently arrests HepG2 cells in M phase and inhibits liver carcinogenesis in DMH-induced rats - Dhania Novitasari, Jun-ya Kato, Muthi’ Ikawati, Dyaningtyas Dewi Pamungkas Putri, Febri Wulandari, Sitarina Widyarini, Ummi Maryam Zulfin, Dhiya Ulhaq Salsabila, Edy Meiyanto (Journal of Applied Pharmaceutical Science, 2023)
Pentagamavunone-1 (PGV-1) has been reported to eliminate cancer cell progression in the breast, blood, and colon. The current approach evaluates its antiproliferative effects and cellular activity against hepatocellular carcinoma cells (HCC). We used the HepG2 cells as an in vitro model for HCC, and PGV-1 was tested for its effects on cell viability, cell cycle modulation, senescence induction, reactive oxygen species (ROS) generation, and cell migration. Moreover, the ability of PGV-1 to prevent liver carcinogenesis was tested in 1,2-dimethylhydrazine- (DMH-) induced rats. PGV-1 irreversibly inhibited cell proliferation via mitotic arrest and cellular senescence. The ROS production was enhanced during the earlier hours of incubation with the compound. Later, PGV-1 significantly delayed the HepG2 cell migration and invasion. Furthermore, PGV-1 prevented steatohepatitis upon DMH administration and drastically reduced the Ki-67 expression in DMH-induced rat liver, indicating its ability to suppress aberrant liver cell proliferation. These findings add to the evidence that PGV-1 could be further developed pharmaceutically as a candidate for cancer therapy with a specific target on mitosis.
Keywords: Curcumin analog (PGV-1), liver cancer, mitotic arrest, anti-carcinogenesis